Osteotomía de miembros inferiores como tratamiento para la acondroplasia - Otero Guerrero, Jose Julián (2025)
Achondroplasia is a genetic condition that affects bone growth, resulting in dwarfism with short limbs and an increased risk of orthopedic complications. Lower limb osteotomy is a surgical treatment used for this condition, aiming to improve bone alignment and length, thereby enhancing mobility and reducing associated musculoskeletal issues. Objective: To conduct an updated literature review on the impact of osteotomy treatment for achondroplasia in the lower limbs to improve the quality of life for these patients. Methods: A cross-sectional descriptive study was carried out using theoretical and empirical knowledge-level methods. Results: The study highlighted the importance of a personalized approach to treating achondroplasia, considering factors such as age, degree of deformity, and the patient's bone development. The study also emphasized the potential of advanced surgical techniques, such as the use of external fixators and technologyassisted surgery, which can improve precision and reduce long-term complications. Conclusions: Lower limb osteotomy as a treatment for achondroplasia is effective when applied appropriately and in a personalized manner. The integration of new technologies and advanced surgical approaches promises improvements in functional outcomes, which could transform patients' lives, allowing too perfect of surgical techniques, as well as the importance of a holistic approach that considers both the physical and emotional aspects of the condition.